Perancangan Sistem Pengembalian Berkas Rekam Medis Tidak Lengkap Berbasis Web di RSUD Dr. Dradjat Prawiranegara Kabupaten Serang - Edy Susena; Marisa Putri Salsabila; Sattari Khoirunnisa; Inayatul Muawanah; Wa Ode Wine (Inovasi Kesehatan Global, 2025)
Incomplete medical records remain a significant challenge in achieving efficient and accountable healthcare services. This study aims to design a web-based return system for incomplete medical records at the Medical Record Installation of RSUD dr. DradjatPrawiranegara, Serang Regency. Using data collection through observation, interviews, and literature review, the system is designed to document incompleteness, return processes, and file status tracking digitally. The design results show that the system can speed up the identification and reporting process of incomplete records, improve staff efficiency, and facilitate auditing and archiving. The conclusion is that a web-based system can serve as a strategic solution in managing incomplete medical documents.